การวิจัยปฏิบัติการในชั้นเรียนเพื่อพัฒนาการเรียนการสอน - แสงเลิศอุทัย จิตติรัตน์; มณีรัตน์ ชัยยุธ (Journal of Research and Curriculum Development, 2019)
The purpose of academic article is presented the main point of classroom action research for learning development which consists of classroom action research particularities, factors influencing of classroom action research, format and process of classroom action research, research presentation for developing student and classroom action research ethics. This academic article is distributed to academician and interested person who apply both to use in their research and developing academic profession for learning principle development.